2022
DOI: 10.1002/nop2.1563
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to chronic obstructive pulmonary disease patients' functional performance: Structural equation modelling based on theory of unpleasant symptoms

Abstract: Aim This study aimed to predict the functional performance of patients with chronic obstructive pulmonary disease by clarifying the relationship among disease severity, uncertainty, social support, symptom experience, coping, and functional performance. Design A model‐testing design was used. Methods The subjects of this study were outpatients with chronic obstructive pulmonary disease who visited the respiratory clinic of a general hospital in Seoul, Korea. The data were collected using validated instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Self-efficacy and self-care behavior, including adherence, showed consistent improvement when participants reported greater social support in six articles [19,28,[30][31][32]35]. In a qualitative study, Chen et al demonstrated a positive association between social support and self-management [28].…”
Section: Associations Between Social Support and Proms In Copd Patientsmentioning
confidence: 95%
See 3 more Smart Citations
“…Self-efficacy and self-care behavior, including adherence, showed consistent improvement when participants reported greater social support in six articles [19,28,[30][31][32]35]. In a qualitative study, Chen et al demonstrated a positive association between social support and self-management [28].…”
Section: Associations Between Social Support and Proms In Copd Patientsmentioning
confidence: 95%
“…In another article, the support of social groups provided mutual trust, support, and increased self-confidence and motivation for self-care [32]. The greater the level of social support received by individuals, the more effective their coping mechanisms became [19]. The Duke-UNC Functional Social Support questionnaire identified social support as a significant factor in the process of living with the illness, as evaluated by the Living with Chronic Illness Scale (LW-CI Scale), which encompasses acceptance, coping, self-management, integration, and adjustment [31].…”
Section: Associations Between Social Support and Proms In Copd Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…This could mean that social support has the potential to influence PROMs, given its association with all these aspects and symptoms of COPD, including the sleep disturbances [ 21 , 30 , 31 ]. Considering the potential influence of adequate social support on patients with COPD [ 32 ], it is logical to assume that higher levels of perceived social support could positively impact a range of PROMs for these patients [ 32 ]. Nevertheless, there is a lack of comprehensive studies in the literature that sufficiently explore the association between perceived social support and self-reported health in patients with COPD using PROMs, particularly in primary care settings [ 33 ].…”
Section: Introductionmentioning
confidence: 99%